Rights to Plant Genetic Resources and Traditional Knowledge Basic Issues and Perspectives - Biber-Klemm, Susette (CABI, 2014)
For centuries, plant genetic resources have provided the basis of civilization and agriculture, of life, health and prosperity around the globe. Knowledge and experience have been passed from generation to generation by custom. Whereas seeds in themselves were the primary objects of earlier trade, dissemination and exchange, more recently plant genetic resources have also come to be addressed in terms of rights to genetic information and their appropriation. Different forms of intellectual property have emerged and altered traditional patterns of exchange and dissemination. The Green Revolution in the 1960s greatly enhanced productivity and formalized the sector. The recent advent of biotechnology has added new dimensions and challenges. Customary patterns of breeding and conservation, still alive in many quarters of the world, are now faced with the impact of modern technology. A new interface is called for – another generation of legal foundations – well beyond national jurisdictions. A new topic has emerged in international law and policy. It is far from settled.